2020
DOI: 10.1007/s10488-020-01044-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Telepsychiatry in Response to COVID-19—Moving Toward 21st Century Access to Care

Abstract: The COVID-19 pandemic threatens to disrupt the provision of mental health services. In response, policymakers, administrators, and providers have taken bold steps toward enabling telepsychiatry to bridge this sudden gap in care for our most vulnerable populations. With rapid deregulation and adoption of this modality of care, careful consideration of issues related to policy and implementation is essential to maximize its effectiveness and mitigate unintended consequences. Though the crisis places the healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 9 publications
2
94
0
3
Order By: Relevance
“… 7 , 8 Finally, quarantine poses social and economic consequences, increasing the usual barriers to seeking care. 6 During previous lockdowns, young adults (aged 16-24 years) had been shown to be especially at risk of mental health issues. 9 During the initial stage of the COVID-19 epidemic, Wang et al 10 found that students in China were at a greater risk of stress, anxiety, and depression in response to the COVID-19 outbreak than older adults.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Finally, quarantine poses social and economic consequences, increasing the usual barriers to seeking care. 6 During previous lockdowns, young adults (aged 16-24 years) had been shown to be especially at risk of mental health issues. 9 During the initial stage of the COVID-19 epidemic, Wang et al 10 found that students in China were at a greater risk of stress, anxiety, and depression in response to the COVID-19 outbreak than older adults.…”
Section: Introductionmentioning
confidence: 99%
“…With COVID-19, this interest in digital health has surged, and the need to expand access to care through smartphones has become patent. Smartphone apps have been proposed as tools to mitigate social isolation, lack of access to care, and other triggers caused by the pandemic [ 3 - 5 ]. Researchers have already demonstrated that access to and use of technology among people with psychosis is nearly equivalent to that in the general population [ 6 - 8 ], but less is known about the actual efficacy of apps in care.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, access to direct emergency and outpatient psychiatric care was reduced ( Hao et al, 2020 ). Consequently, mental health practitioners and policymakers called for research on regulations and implementations of alternative clinical interventions, such as telepsychiatry ( Kannarkat et al, 2020 ; Shore et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%